2018
DOI: 10.1002/cncy.21981
|View full text |Cite
|
Sign up to set email alerts
|

The impact of noninvasive follicular thyroid neoplasm with papillary‐like nuclear features on the rate of malignancy for atypia of undetermined significance subcategories

Abstract: A subset of resected AUS nodules can be reclassified as NIFTP, and that significantly decreases the ROM, especially for AUS-N and AUS-F. Nonetheless, AUS-N still harbors a substantially higher ROM than AUS-F. Cancer Cytopathol 2018;126:309-16. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In 2016, the new terminology of noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) was been proposed to replace the noninvasive encapsulated follicular variant of papillary thyroid carcinoma (PTC) [17] and this has been further adopted by the 2017 World Health Organization Classification of Tumors of Endocrine Organs [18]. The change in tumor classification inevitably influences the preoperative thyroid FNA diagnosis [19] and the utilization of molecular testing [20]. However, an international multi-institutional study from India, Japan, South Korea, Taiwan, and Thailand revealed a less significant impact of NIFTP reclassification on the practice of thyroid cytopathology [21].…”
Section: Impact Of Noninvasive Follicular Thyroid Neoplasm With Papilmentioning
confidence: 99%
“…In 2016, the new terminology of noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) was been proposed to replace the noninvasive encapsulated follicular variant of papillary thyroid carcinoma (PTC) [17] and this has been further adopted by the 2017 World Health Organization Classification of Tumors of Endocrine Organs [18]. The change in tumor classification inevitably influences the preoperative thyroid FNA diagnosis [19] and the utilization of molecular testing [20]. However, an international multi-institutional study from India, Japan, South Korea, Taiwan, and Thailand revealed a less significant impact of NIFTP reclassification on the practice of thyroid cytopathology [21].…”
Section: Impact Of Noninvasive Follicular Thyroid Neoplasm With Papilmentioning
confidence: 99%
“…There was also considerable variability in AUS/FLUS utilization at different centers, with reporting rates that range from 3.1%‐59.4% (Table 2). The largest studies included into the systematic analysis consisting of the largest number of case series (totally 5132 cases with histopathological correlations) are reported by Evranos 23 Topaloğlu et al, 24 Hyeon et al, 25 Kim et al, 14 Mosca et al, 1 Jan et al, 26 Faquin et al, 27 Ho et al, 28 , Türkyılmaz et al, 2 Mathur et al, 12 Hang et al 29 Li et al, 30 Renshaw, 31 Kiernan et al, 32 and VanderLaan et al 33 and are listed in the same order within Table 2 including their reported data.…”
Section: Resultsmentioning
confidence: 99%